The Effects of Vignette Placement on Attitudes Toward Supporting Family Members. Issue 1 (February 2016) - Lau, Charles Q.; Seltzer, Judith A.; Bianchi, Suzanne M.
Vignettes are useful for measuring norms and beliefs, but little is known about how vignette placement affects responses to subsequent attitude questions. We investigate how the placement of a vignette about parents and adult children living together affects answers to subsequent questions about family obligations in a survey of the U.S. population. We randomly assigned the order of the vignette and three single-statement attitude questions. For the single-statement question about family members living together, the effect of vignette placement depended on respondents' original attitudes. For individuals with ambivalent or positive attitudes, asking the vignette before the attitude questions doubled reports of favorable attitudes. Vignette placement had no effect for those with negative attitudes. For the single-statement attitude questions about financial support between parents and adult children, vignette placement had no effect, suggesting that vignette placement may only influence subsequent questions about the same topic.